Influencia del estado emocional en el aprendizaje de estudiantes de 2do EGB de la Escuela “Isabel la Católica” Guaranda, 2025. - Guerrero Segura, Joselyn Mireya (2025)
To have children with an encouraging emotional state, it is important to take the reins from the family and educators, who are the fundamental pillar where emotional skills are learned, since children observe and absorb how parents manage their emotions and relationships. Therefore, parents and teachers not only educate through direct instructions, but also through their example in managing feelings and conflicts. This research work allows an in- depth analysis of the problem of the emotional state of children at the Isabel la Católica School in the Parish of Guanujo, involving 28 children and one teacher, for which a topic entitled: Influence of the emotional state on the learning of 2nd EGB students of the "Isabel la Católica" school Guaranda, 2025. The objectives set out try to find a solution to all this research in order to improve the emotional state of children, likewise this research is supported by the theoretical framework that scientifically reinforces this entire research process, based on authors with very scientifically advanced cognitive criteria in terms of emotional state and learning. Then, to complement it, research methods and techniques were used that contributed to data collection, where the teacher was interviewed and the Pata Negra Projective Test instrument was applied to the children of the second grade of Basic Education of the Isabel la Católica School and complemented with their respective conclusions.